ANALYSIS OF THE FACTORS THAT INFLUENCE POVERTY IN THE DISTRICTS/CITIES OF YOGYAKARTA SPECIAL REGION - Hasanah, Nuryana Nurul; Priyadi, Unggul (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to identify the key factors influencing poverty in the districts/cities of Yogyakarta from 2010 to 2019 using panel data regression analysis. The Fixed Effect Model was determined to be the most appropriate for this analysis. The findings reveal that the Human Development Index (IPM), average years of schooling, open unemployment rate, and minimum wage are significant determinants of poverty in the region. The model explains 99.54% of the variation in poverty levels (R² = 0.9954). These results underscore the importance of targeted policy interventions in education, employment, and wage regulation to effectively reduce poverty in Yogyakarta.